Forest management and regional tree composition drive the host preference of saproxylic beetle communities. Issue 3 (22nd March 2015) - Müller, Jörg; Wende, Beate; Strobl, Carolin; Eugster, Manuel; Gallenberger, Iris; Floren, Andreas; Steffan‐Dewenter, Ingolf; Linsenmair, Karl Eduard; Weisser, Wolfgang W.; Gossner, Martin M.; Baraloto, Christopher
Summary Among saproxylic beetles, many early colonizers prefer particular host species. Ranking of preferred hosts of local saproxylic beetle communities is critical for effective dead‐wood management in forests, but is rarely done because experiments with numerous tree species are labour and cost intensive. We analysed the host preference of local saproxylic beetle communities on logs of 13 tree species in relation to management (unmanaged and managed beech stands, conifer plantations on natural beech sites) in three regions of Germany during the most critical period for host specificity, that is the first two years after harvesting. Hosts were ranked quantitatively based on the ordinal ranking of hosts by single beetle species, which in turn was based on the variation in beetle abundance. First, we employed a Bradley–Terry model in which ranking was derived from paired comparisons of host trees. Then, a model‐based recursive partitioning of the Bradley–Terry model tested whether host preference of beetle communities is affected by stand management, region and decay progress of dead wood. Our results indicated that beetle communities overall avoided logs of Fraxinus, Pseudotsuga, Larix and Tilia, and Carpinus ranked highest in preference. Carpinus also ranked highest for communities of broadleaf specialists; Picea abies ranked highest for communities of conifer specialists. Model‐based recursive partitioning revealed that ranking of local hosts in conifer stands differed from that of broadleaf stands, and that ranking of hosts in broadleaf stands differed between regions, but only in the first year for both. Synthesis and applications. Early‐colonizing saproxylic beetle communities vary locally in their choice of host trees. Therefore, forest managers should focus on the enrichment of dead wood of regional tree species and tree species of the local stand to successfully promote early‐colonizing beetle.